2015
DOI: 10.1111/jpi.12245
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin regulates carbohydrate metabolism and defenses against Pseudomonas syringae pv. tomato DC3000 infection in Arabidopsis thaliana

Abstract: Melatonin has been reported to promote plant growth and development. Our experiments with Arabidopsis thaliana showed that exogenous applications of this molecule mediated invertase inhibitor (C/VIF)-regulated invertase activity and enhanced sucrose metabolism. Hexoses were accumulated in response to elevated activities by cell wall invertase (CWI) and vacuolar invertase (VI). Analyses of sugar metabolism-related genes revealed differential expression during plant development that was modulated by melatonin. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 126 publications
(113 citation statements)
references
References 84 publications
3
110
0
Order By: Relevance
“…A higher total C concentration induced SPS and HxK activity in the leaves in Ps with abundant N supply, which indicated that C metabolism is stimulated by a sufficient N supply (Figure 3D). Indeed, it has also been shown in other plants that an increase in protein biosynthesis results in a greater demand for C skeletons [28,29]. However, the activities of HxK, CWI, and VI in the Ps roots were induced with low N supply, suggesting accelerated glycogen metabolism and respiration in the Ps roots in response to N deficiency.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A higher total C concentration induced SPS and HxK activity in the leaves in Ps with abundant N supply, which indicated that C metabolism is stimulated by a sufficient N supply (Figure 3D). Indeed, it has also been shown in other plants that an increase in protein biosynthesis results in a greater demand for C skeletons [28,29]. However, the activities of HxK, CWI, and VI in the Ps roots were induced with low N supply, suggesting accelerated glycogen metabolism and respiration in the Ps roots in response to N deficiency.…”
Section: Discussionmentioning
confidence: 91%
“…However, little is known about transcriptional regulation in trees at deficient and sufficient N levels. Previous studies have detected higher expression, downregulation, or stable transcript levels of key genes involved in C/N metabolism in various poplar species in response to low and/or sufficient N levels [28,39]. The transcriptional downregulation of SUS1 and SPS in response to N deficiency indicates that C metabolism is inhibited due to a limited N supply.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a link between melatonin and sugar metabolism and signaling has been suggested in the context of biotic stress (Zhao et al, 2015). Recently, Jiao et al (2016) isolated endophytic bacterial strains that live in the plant apoplast and secrete melatonin.…”
Section: Damp Mixtures For Multistress Resistancementioning
confidence: 99%
“…Also, melatonin as well as its metabolites can eliminate different kinds of ROS including superoxide anion (O2), hydrogen peroxide (H 2 O 2 ), hydroxyl radical ( • OH), singlet oxygen ( 1 O 2 ), peroxynitrite anion (ONOO - ) and nitric oxide (NO) (Tan et al, 2013). Melatonin has been reported to protect plants against a variety of abiotic and biotic stresses (Zuo et al, 2014; Liang et al, 2015; Liu et al, 2015; Shi et al, 2015a; Wang et al, 2015; Zhao et al, 2015b; Li C. et al, 2016; Xu et al, 2016). The transgenic Arabidopsis plants, ecotopically expressing melatonin synthetic gene MzASMT1 , had higher endogenous melatonin production and significantly lower ROS than that of their wild types.…”
Section: Introductionmentioning
confidence: 99%